Raising Backyard Poultry in Rural Bangladesh: Financial and Nutritional Benefits, but Persistent Risky Practices. Issue 5 (16th June 2016) - Shanta, I. S.; Hasnat, Md. A.; Zeidner, N.; Gurley, E. S.; Azziz‐Baumgartner, E.; Sharker, M. A. Y.; Hossain, K.; Khan, S. U.; Haider, N.; Bhuyan, A. A.; Hossain, Md. A.; Luby, S. P.
Summary: Poultry is commonly raised by households in rural Bangladesh. In 2007, the Government of Bangladesh began a mass media campaign to disseminate 10 recommended precautions to prevent transmission of H5N1 from poultry to humans. This longitudinal study explored the contribution of backyard poultry on household economy and nutrition and compared poultry‐raising practices to government recommendations. From 2009 to 2012, we enrolled a nationally representative sample of 2489 primary backyard poultry raisers from 115 rural villages selected by probability proportional to population size. Researchers interviewed the raisers to collect data on poultry‐raising practices. They followed the raisers for 2–12 months to collect data on household income and nutrition from poultry. Income from backyard poultry flocks accounted for 2.8% of monthly household income. Return on annual investment (ROI) per flock was 480%. Yearly, median family consumption of eggs was one‐fifth of the total produced eggs and three poultry from their own flock. Respondents' reported practices conflicted with government recommendations. Sixty per cent of raisers had never heard of avian influenza or 'bird flu'. Among the respondents, 85% handled sick poultry or poultry that died due to illness, and 49% slaughtered or defeathered sick poultry. In 37% of households, children touched poultry. Fifty‐eight per cent never washed their hands with soap after handling poultry, while <1% covered their nose and mouth with a cloth when handling poultry. Only 3% reported poultry illness and deaths to local authorities. These reported practices did not improve during the study period. Raising backyard poultry in rural Bangladesh provides important income and nutrition with an excellent ROI. Government recommendations to reduce the risk of avian influenza transmission did not impact the behaviour of poultry producers. Further research should prioritize developing interventions that simultaneously reduce the risk of avian influenza transmission and increase productivity of backyard poultry.